Application status and prospects of robotic transanal minimally invasive surgery - Huang Bin; Li Fan; Tong Weidong (结直肠肛门外科)
Transanal minimally invasive surgery (TAMIS) has been widely applied in the surgical treatment of benign rectal diseases and some malignant tumors. However, regardless of whether it is transanal endoscopic microsurgery (TEM), transanal minimally invasive surgery (TAMIS), or transanal total mesorectal excision (taTME), the difficulty of operating in the narrow space of the anorectum and the relatively long learning curve have constrained the development of these surgical techniques. The robotic surgical system overcomes many limitations of traditional laparoscopy, particularly its advantages in narrow spaces, which have brought new vitality to the development of transanal minimally invasive surgery. In recent years, research on robotic surgery has continued to increase, with some preliminary results achieved in terms of surgical feasibility, safety, and short-term postoperative outcomes. This article briefly elaborates on the current application status and development prospects of surgical robots in TAMIS, focusing primarily on the da Vinci® robotic system.